HUMAN’23: 6th Workshop on Human Factors in Hypertext - Rubart, Jessica; Atzenbeck, Claus (Proceedings of the 34th ACM Conference on Hypertext and Social Media)
HUMAN 2023 is the 6th workshop of a series for the ACM Hypertext conferences. The HUMAN workshop has a strong focus on the user and thus is complementary to the strong machine analytics research direction that could be experienced in previous conferences.The user-centric view on hypertext not only includes user interfaces and interaction, but also discussions about hypertext application domains as well as human-centered AI. Furthermore, the workshop raises the question of how original hypertext ideas (e. g., Doug Engelbart’s "augmenting human intellect" [7] or Jeff Conklin’s "hypertext as a computer-based medium for thinking and communication" [6]) can improve today’s hypertext systems.
Keywords: user interfaces; information structuring; decision making; human-centered AI; cognitive aspects; scientific community; digital humanities; user interaction; human factors; user-centric; annotation; adaptive hypertext; hypermedia; collaboration; information systems; augmentation; hypertext; communication; intercultural aspects